Engineering entrepreneurship from idea to business plan a guide for innovative engineers and scientists - Swamidass, Paul M. (New York, NY Cambridge University Press, 2016)
"This book is for engineers and scientists who have the aptitude and education to create new products that could become income-producing businesses for themselves and for investors. The book uses short chapters and gets directly to the point without lengthy and distracting essays. The rapid growth in technology-based business plan contests is a clear sign that there are many wealthy inventors looking to make substantial investments in start-ups based on new inventions by inventors, who lack the funds and knowledge to start a business. The key features of this reference enable readers to sharpen their new idea, turn an idea into a commercial product, conduct patent search and complete a provisional patent application, and collect requisite data and prepare a business plan based on a carefully selected business model. Supporting materials are provided on the book's extensive website (www.engineer-entrepreneur-book.com/)." -- Publisher's description.
Engineers create value for investors -- Introduction to technological innovation -- The seven phases of technological innovation -- Engineers add value in stages -- Disruptive technological innovators : value creators -- Ideas : how do you find them? -- Turn your idea into a product -- Early detection of market potential / A. David Mixson -- Illustrative case : tennis racquet customer needs survey -- What engineers can do for product development -- Intellectual property, patents and trade secret -- If you cannot afford a patent attorney -- Reading and learning from a granted US patent -- Patent search and conclusions before drafting a patent application -- Pro se US patent applications do succeed -- Macroeconomics for innovators in engineering and science -- Customers, target markets and marketing -- The power of social media marketing / Haitham A. Eletrabi -- Market analysis resources -- Illustrative case : market analysis for tennis racquets -- Competition research -- Manufacturing and sourcing -- Break-even analysis -- Sales and distribution : wholesale, direct and other -- Reaching your customer : advertising and promotion -- Selecting the pre-start-up model -- Key decisions : costs estimation and pricing -- The business model versus the business plan -- The business plan : the end of phase 3 -- A business plan is a war plan : anything can change -- Making the start-up business financially feasible -- What angel investors look for in a phase 4 company seeking funding -- Ethics in engineering and business professions -- Business as a legal entity in the United States -- Pre-start-up business organization and management -- An illustrative case : Amazon.com as a start-up -- Execution phases 4 to 6 -- Phase 7 : six case studies of mature firms -- Comparing phase 7 firms from different industries : Apple and Walmart -- Teams and teamwork -- Leadership issues in start-up business / Jay Clark -- What we know about entrepreneurs -- Creating value as an engineer in India / Hephzibah Stephen -- Technology licensing option for inventors.
Includes bibliographical references (pages 231-234) and index.
Keywords: Engineering -- Vocational guidance; New business enterprises; Entrepreneurship; Business planning